Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Di Kelas XI-IPA SMA Islam Al-Ulum Terpadu Medan - Tri Wulan Sari (Balai Diklat Keagamaan Medan, 2021)
The aim of this research is (1) to know the implementation strategy of Problem Based Learning (PBL) that is used to improve mathematically ability students in the Linear Progamming (2) to know the increasing of mathematically ability students in the Linear Progamming in class XI-IPA SMA Islam Al-Ulum Terpadu Medan T.A 2016/2017 after the implementation of Problem Based Learning (PBL) material Linear Progamming in class XI-IPA SMA Islam Al-Ulum Terpadu Medan T.A 2016/2017. Subjects in this research were students of class XI-IPA SMA Islam Al-Ulum Terpadu Medan T.A 2016/2017 totaling 38 students and the object of this study is used to improve mathematically ability students in the Linear Progamming in class XI-IPA SMA Islam Al-Ulum Terpadu Medan T.A 2016/2017. The research instrument used is observation, tests and documentation. From the test mathematically ability results, it can be concluded that the implementation strategy of Problem Based Learning (PBL) that is used to improve mathematically ability students in the Linear Progamming in class XI-IPA SMA Islam Al-Ulum Terpadu Medan T.A 2016/2017.